Contribution of Islamic Education Values in Marriage Tradition of Banggai Ethnic, Indonesia - Oyan D. Taufik; Sagaf S. Pettalongi; Sidik Sidik (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2020)
The aim of this article is to find out the contribution of Islamic education values in marriage according to the customs of the tribe in district of Banggai Bulagi. This study used qualitative method. While the data was gathered through direct observation, interviews, and document. The results show that (1) the tradition of pasai is carried out with the intention of fulfilling the provisions of the applicable customs and helping to meet the costs of holding the wedding party in the women's family. (2) implementation of marriage according to the customs of the Bulagi tribe only through poiyas stage. Then the realization of the values of the Islamic education in marriage according to the customs of the tribe of Banggai district of Bulagi consists of three extant value i.e. value of belief, value of equality, and the value of morals. (3) A marriage according to the Banggai customs, carried out in accordance with customary paths and stages, is more steady in understanding the values ​​of Islamic education. The implication of this research is, the role of religious figures, custom figures, public figures, are very influential on society of the tribe in the village of Banggai Bulagi to keep the value of education of Islam applied in any tradition and instilling the teachings of Islamic religion to the younger generation to avoid pregnancy outside of marriage.